SMART DENTAL ALARM AS EDUCATIVE MEDIA IN INCREASING KNOWLEDGE AND BEHAVIOR OF TOOTHBRUSHING IN EARLY CHILDHOOD - Ratna, Dewi; Djamil, Masrifan; Wiyatini, Tri; Supriyana, Supriyana; Sunarjo, Lanny (Postgraduate Program , Poltekkes Kemenkes Semarang, 2021)
Early childhood suffer from very high dental and oral health problems. This problem is caused by poor knowledge and behavior of tooth brushing. An effort toincrease the knowledge and behavior of tooth brushing requires innovative media as per the age and parental assistance. This researce aims to develop innovative dental health education media to increase knowledge and behavior of preschool children. We undertook this study using Research and Development method with the stages of information collection, product build, validation by experts and finished product. The number of samples was 30 for each intervention and control group with a random sampling technique. Data were tested using ISO 9126, chi-square, Shapiro Wilk, Friedman and Man Whitney. The results of this study indicate that Smart Dental Alarm is more effective in increasing the knowledge and behavior of the tooth brushing behavior in preschool children than using power point regarding the pre-test, post-test 1 and 2 which obtain p-Value in 0.000. Smart Dental Alarm is more effective than power point because it is equipped with various features or media types that are intended to increase knowledge and behavior while power point only contains material with pictures.